Relación entre la ejecución de ingresos y la ejecución de inversiones en la Municipalidad Distrital de Belén 2017-2024 - Alvarez Ramirez, Martin Manuel (2025)
The study is based on enriching the understanding of financial management in local governments, specifically focusing on the association between revenue execution and investment execution in the District Municipality of Belén from the second quarter of 2017 to the third quarter of 2024. Exploring topics such as the public budget, the regulatory framework of public revenues and public investment, this study contributes to the development of theories and models that explain how financial resources are managed in municipalities. The present research is quantitative, correlational level and non-experimental in design with longitudinal data. It was observed that, despite an increasing behavior in the execution of income and the execution of investments in the District Municipality of Belén, no significant relationship was found between them. Otherwise, when disaggregating income and investments by financing sources, it was found that the determined resources represented 79.06% of the income collection, but only 35.67% of the accumulated capital expenses. With respect, it was determined that there is a direct relationship of 37.82% between the execution of income for certain resources and the execution of investments for certain resources in the institution.